Achieving Product Ambidexterity in New Product Development: The Role of Middle Managers' Dynamic Managerial Capabilities - Andrea Greven; Sebastian Kruse; Anne Vos; Steffen Strese; Malte Brettel (Journal of Management Studies, 2022)
While the concept of dynamic managerial capabilities was initially developed to understand top managers' strategic decisions, we theorize that it can explain how middle managers successfully contribute to functional outcomes. In this paper, we apply the dynamic managerial capabilities perspective and theorize that middle managers' capabilities to sense, seize, and reconfigure opportunities and assets, enhance product ambidexterity. We test our predictions with survey data obtained in two waves with a three-year time lag and enriched with archival data from a sample of 185 German middle managers. Our results show that middle managers' general human capital (specialized education), structural social capital (managerial ties), and relational social capital (trust) are positively related to product ambidexterity, while their cognitive social capital (solidarity) is negatively related. We contribute by expanding the concept of dynamic managerial capabilities to middle management and provide insights into the underexplored relationship between middle managers' capabilities and functional product ambidexterity.
Keywords: 650; dynamic managerial capabilities; middle management; NPD function; product ambidexterity; SMEs